Clinical and Molecular Findings in Mendelian Susceptibility to Mycobacterial Diseases: Experience From India - Taur, Prasad D.; Gowri, Vijaya; Pandrowala, Ambreen Abdulwahab; Iyengar, Vaishnavi V.; Chougule, Akshaya; Golwala, Zainab; Chandak, Shraddha; Agarwal, Reepa; Keni, Purva; Dighe, Neha; Bodhanwala, Minnie; Prabhu, Shakuntala; et al. (Frontiers in Immunology, 2021)
Mendelian Susceptibility to Mycobacterial diseases (MSMD) are a group of innate immune defects with more than 17 genes and 32 clinical phenotypes identified. Defects in the IFN-γ mediated immunity lead to an increased susceptibility to intracellular pathogens like mycobacteria including attenuated Mycobacterium bovis-Bacillus Calmette-Guérin (BCG) vaccine strains and non-tuberculous environmental mycobacteria (NTM), Salmonella, fungi, parasites like Leishmania and some viruses, in otherwise healthy individuals. Mutations in the IL12RB1 gene are the commonest genetic defects identified. This retrospective study reports the clinical, immunological, and molecular characteristics of a cohort of 55 MSMD patients from 10 centers across India. Mycobacterial infection was confirmed by GeneXpert, Histopathology, and acid fast bacilli staining. Immunological workup included lymphocyte subset analysis, Nitro blue tetrazolium (NBT) test, immunoglobulin levels, and flow-cytometric evaluation of the IFN-γ mediated immunity. Genetic analysis was done by next generation sequencing (NGS). Disseminated BCG-osis was the commonest presenting manifestation (82%) with a median age of presentation of 6 months due to the practice of BCG vaccination at birth. This was followed by infection with Salmonella and non-typhi Salmonella (13%), Cytomegalovirus (CMV) (11%), Candida (7%), NTM (4%), and Histoplasma (2%). Thirty-six percent of patients in cohort were infected by more than one organism. This study is the largest cohort of MSMD patients reported from India to the best of our knowledge and we highlight the importance of work up for IL-12/IL-23/ISG15/IFN-γ circuit in all patients with BCG-osis and suspected MSMD irrespective of age.